A new species of Hemiphyllodactylus Bleeker (Squamata; Gekkonidae) from Peninsular Thailand that converges in morphology and color pattern on Pseudogekko smaragdinus (Taylor) from the Philippines - Grismer, L. Lee; Yushchenko, Platon V.; Pawangkhanant, Parinya; Naiduangchan, Mali; Nazarov, Roman A.; Orlova, Valentina F.; Suwannapoom, Chatmongkon; Poyarkov, Nikolay A. (Zootaxa, 2020)
An integrative taxonomic analysis of newly discovered populations of Hemiphyllodactylus from Indochina recovered a new species from Peninsular Thailand and two others from Laos. The new Thai species, Hemiphyllodactylus pardalis sp. nov. described herein, is the sister species to all other species in the newly designated Indochina clade and has a unique spotted contrasting dorsal pattern not seen in any other species of Hemiphyllodactylus. This, along with its elongate and gracile body morphology, renders it remarkably convergent on the Philippine gecko Pseudogekko smaragdinus despite the fact it is deeply nested within Hemiphyllodactylus. The description of this new species underscores the depauperate nature of Hemiphyllodactylus diversity throughout Indochina in general and Thailand in particular compared to neighboring upland areas of Myanmar and Peninsular Malaysia. This especially underscores the need for continued herpetofaunal field surveys in montane areas of western Thailand.